2019
DOI: 10.1017/s0022215119000513
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dysphagia in patients with muscle tension dysphonia

Abstract: BackgroundIt is hypothesised that patients with muscle tension dysphonia have a high prevalence of dysphagia in comparison to normative values reported in the literature.MethodsThis prospective study included 44 subjects diagnosed with muscle tension dysphonia, based on symptoms and laryngoscopic findings, and 25 control subjects with no history of dysphonia and normal laryngeal examination findings. Demographic data included age, gender and smoking history. The aetiology of muscle tension dysphonia was classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
2
0
3
Order By: Relevance
“…De los 15 artículos restantes, tres se refieren a la necesidad de realizar más exploración instrumentada y una adecuada historia clínica para llegar a un oportuno diagnóstico. Dos estudios refieren mayor patología en mujeres que en hombres [5,9]; cuatro reportan presión subglótica aumentada (>90 mmHg) [10][11][12][13] y tres reportan medidas fonatorias [12][13][14]: uno encuentra diferencias significativas [12] y dos refieren solo el pico cepstral como referencia confiable y con mayor predictibilidad diagnóstica [13,14]. Un trabajo propone el video de alta resolución como demostración de hiperfunción vocal [15].…”
Section: Resultsunclassified
See 2 more Smart Citations
“…De los 15 artículos restantes, tres se refieren a la necesidad de realizar más exploración instrumentada y una adecuada historia clínica para llegar a un oportuno diagnóstico. Dos estudios refieren mayor patología en mujeres que en hombres [5,9]; cuatro reportan presión subglótica aumentada (>90 mmHg) [10][11][12][13] y tres reportan medidas fonatorias [12][13][14]: uno encuentra diferencias significativas [12] y dos refieren solo el pico cepstral como referencia confiable y con mayor predictibilidad diagnóstica [13,14]. Un trabajo propone el video de alta resolución como demostración de hiperfunción vocal [15].…”
Section: Resultsunclassified
“…Un trabajo que evaluó 44 pacientes con diagnóstico de MTD por hallazgos laringoscópicos, reportó que la edad media de los pacientes fue de 45,93 ± 14,95 años, con una relación mujer/hombre de 1.2:1. Entonces, la presentación es mayor en adultos de más de 30 años y ligeramente mayor en mujeres [5]. El estudio de Benninger et al con población de Estados Unidos de América, evalúo 146,7 millones de personas, entre 2008 a 2012, estimando la prevalencia de disfonía para 2008 de 760,265 casos y para 2012 de 1,247,471, con aumento del 1.3 % al 1.7 %, en estos años [6].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Given our knowledge of other symptoms of Long COVID, dysphagia symptoms may be driven by other factors such as laryngeal hypersensitivity, reflux, post‐extubation dysphagia, muscle tension dysphagia, fatigue and breathlessness (Buckley et al., 2021; Frajkova et al., 2020; Hamdan et al., 2019; Kruser & Prescott, 2017). During the period under study in East Suffolk, access to SLT‐led videonasendoscopy and FEES was limited by the emergence of COVID recovery planning, and implementation of changing professional guidance (RCSLT, 2021b) to facilitate the resumption of clinics.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47][48][49][50][51] Since dysphagia is a known association of muscle tension dysphonia, we postulated that the same therapeutic techniques would be beneficial for a subset of dysphagia patients. 52,53 Our MTDg retrospective study revealed that voice therapy techniques aimed at reducing laryngeal muscle tension significantly reduced dysphagia symptoms. The same therapy techniques were then employed in this perspective study with promising results.…”
Section: Goal and Efficacy Of Therapymentioning
confidence: 94%